Induction of oxidative stress, DNA damage, and apoptosis in a malignant human skin melanoma cell line after exposure to zinc oxide nanoparticles - Alarifi, Saud (Dove Medical Press, 2013)
The widespread use of zinc oxide (ZnO) nanoparticles worldwide exposes humans to their adverse effects, so it is important to understand their biological effects and any associated risks. This study was designed to investigate the cytotoxicity, oxidative stress, and apoptosis caused by ZnO nanoparticles in human skin melanoma (A375) cells. MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazoliumbromide] and lactate dehydrogenase-based cell viability assays showed a significant decrease in cell viability after exposure to ZnO nanoparticles, and phase contrast images revealed that cells treated with these nanoparticles had a lower density and a rounded morphology. ZnO nanoparticles were also found to induce oxidative stress, evidenced by generation of reactive oxygen species and depletion of the antioxidant, glutathione. Induction of apoptosis was confirmed by chromosomal condensation assay and caspase-3 activation. Further, more DNA damage was observed in cells exposed to the highest concentration of ZnO nanoparticles. These results demonstrate that ZnO nanoparticles have genotoxic potential in A375 cells, which may be mediated via oxidative stress. Our short-term exposure study showing induction of a genotoxic and apoptotic response to ZnO nanoparticles needs further investigation to determine whether there may be consequences of long-term exposure to ZnO nanoparticles.